2008
DOI: 10.1521/suli.2008.38.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Farewell to the World: Suicide Notes from Turkey

Abstract: There has been limited study of suicide in Islamic countries. This paper marks the first study of suicide notes in Turkey, an Islamic country. Using a classification scheme, 49 suicide notes (a rate of 34.5%) were studied. The results show that note writers do not differ greatly from other suicides. Further analysis of younger (<40) and older (>40) suicide note writers reveal few significant differences. Our results, together with the results of classification studies in different countries, suggest that cauti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 19 publications
2
28
2
3
Order By: Relevance
“…The reality is that suicide notes are relatively uncommon in the United States and their absence does not indicate anything systematic about the suicide or the decedent. While this study was conducted in one U.S. state, studies of suicide notes in other cultures have yielded disparate and conflicting results about frequency, content, and meaning of notes (e.g., Chavez‐Hernandez, Paramo, Leenaars, & Leenaars, ; Demirel, Akar, Sayin, Candansayar, & Leenaars, ; Haines, Williams, & Lester, ; Wong, Yeung, Chan, Yip, & Tang, ). In addition, a note may not be as meaningful or helpful as many suicide bereaved may wish.…”
Section: Discussionmentioning
confidence: 99%
“…The reality is that suicide notes are relatively uncommon in the United States and their absence does not indicate anything systematic about the suicide or the decedent. While this study was conducted in one U.S. state, studies of suicide notes in other cultures have yielded disparate and conflicting results about frequency, content, and meaning of notes (e.g., Chavez‐Hernandez, Paramo, Leenaars, & Leenaars, ; Demirel, Akar, Sayin, Candansayar, & Leenaars, ; Haines, Williams, & Lester, ; Wong, Yeung, Chan, Yip, & Tang, ). In addition, a note may not be as meaningful or helpful as many suicide bereaved may wish.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is a heterogeneous phenomenon and a number of research methodologies are used to study it including epidemiology, psychological autopsies and coronial records. Although studying suicide notes provides a unique opportunity to understand the motives, psychodynamic factors and state of mind of individuals who proceed to suicide, it has not been studied frequently (Demirel et al, 2008). Suicide notes contain direct information penned by the individual and the quality of the data may be more reflective of their mental state than information obtained from other informants (Ho et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Studies that included in their analyses psychiatric histories and psychiatric hospitalizations reported contradictory findings. Several international studies reported that suicide decedents who had known mental health issues such as mental disorder, history of self‐harm, or recent or prior psychiatric hospitalization were less likely to leave behind a note (Carpenter et al., ; Chia, Chia, & Tai, ; Demirel, Akar, Sayin, Candansayar, & Leenaars, ; Ho et al., ; Howard & Surtees, ; Kuwabara et al., ; Paraschakis et al., ; Salib et al., ; Wong, Yeung, Chan, Yip, & Tang, ). Stack and Rockett (), in their analysis of US data from the National Violent Death Reporting System, found that those with current mental health issues or depression were more likely to have left a suicide note (OR = 1.11 & OR = 1.22, respectively); however, those with current mental health treatment and alcohol abuse‐related problems (15% and 24%, respectively) were less likely to have left a note.…”
Section: Discussionmentioning
confidence: 99%